DEVELOPMENT OF TECHNICAL LEARNING MEDIA MULTIMEDIA BASED VOLLEYBALL IN SMP NEGERI 3 SATU ATAP GEBANG - Indra Kasih; Dian Reza Fauzi Sembiring (Universitas Negeri Medan, 2022)
This research is motivated by the fact that learning volleyball at school is still mostly conventional, such as learning activities at school are still centered on the teacher. The objectives of this study are: To determine the feasibility of Interactive Multimedia-Based Volleyball Learning Media for Junior High School students. This study uses the Research and Development model using the ADDIE development model which includes (1) Analyze , (2) Design , (3) Develop , (4) Implementation . and (5) Evaluate (Evaluation). After this learning media is used in the implementation stage, the learning media is declared fit for use as teaching materials in schools with an average acquisition score of material experts of 3.6 and an average acquisition score of media experts of 3.6, an average acquisition score of trials the moderate group is 3.7 and the student response as a user is 3.8 so that the feasibility of the learning media developed falls into the